Reconfigurable Design of mmWave Liquid-Crystal Frequency Selective Surface at Ka-Band - Chou, Hsi-Hsir; Ke, Guan-Jhou; Lin, Cheng-Chung; Lin, Guo-Sheng (IEEE transactions on electromagnetic compatibility, 2022)
A reconfigurable design of frequency selective surface (FSS) using nematic liquid crystal (LC) materials is reported. The proposed LC-FSS resonates at Ka-band frequencies to provide a bandpass nature. The frequency selection was achieved by altering the dielectric anisotropy of LC materials. This study used a low-cost Merck-E7 LC material with dielectric tunability of nearly 0.45 to study the resonance characteristics. Full-wave simulations have achieved a frequency tunability range of 5.06%. An LC-FSS prototype of 7 cm × 7 cm in size was fabricated for experimental evaluation, consisting of 25 × 25 unit cells. The measurement results show that a maximum frequency tunability close to 4.8% has been achieved for a normally incident illumination of electromagnetic waves. Moreover, the maximum frequency deviations were only 4.73% and 4.94% with/without a bias voltage to shift the center frequency. These experimental results have precisely verified the numerical simulations despite the frequency deviations resulting from the fabrication tolerances.